Maghreb des entrepreneurs : les horizons du Sud - Sylvie Daviet (L’Année du Maghreb)
Maghreb entrepreneurship has received longstanding attention from researchers in the social sciences and has continued to assert itself under the influence of different parameters. In the following lines, the prism of analysis will be the nature and evolution of the Maghreb entrepreneurial dynamics facing Europe. Without neglecting Mediterranean component, these include answering the following questions: what are the conditions for the emergence of these dynamics, in terms of conditions, opportunities, institutional frameworks? What are the relevant entrepreneurs and what networks are mobilized? What strategies are implemented?